Optimal control simulation predicts effects of midsole materials on energy cost of running - Dorschky, E.; Krüger, D.; Kurfess, N.; Schlarb, H.; Wartzack, S.; Eskofier, B. M.; van den Bogert, A. J. (Computer Methods in Biomechanics and Biomedical Engineering, 2019)
Testing sports equipment with athletes is costly, time-consuming, hazardous and sometimes impracticable. We propose a method for virtual testing of running shoes and predict how midsoles made of BOOST affect energy cost of running. We contribute a visco-elastic contact model and identified model parameters based on load-displacement measurements. We propose a virtual study using optimal control simulation of musculoskeletal models. The predicted reduction in energy cost of ~1% for BOOST in comparison to conventional materials is consistent with experimental studies. This indicates that the proposed method is capable of replacing experimental studies in the future.